Conjunctival changes and inflammatory aspects in rabbits' conjunctivas induced by fixed combinations of prostaglandin analogues and timolol maleate - de Faria, Nubia Vanessa Lima (Springer, 2013)
BACKGROUND: The purpose of this research is to compare the histological and immunohistochemical changes induced by fixed combinations of timolol maleate and prostaglandin analogues in the rabbit conjunctiva. Thirty left eyes of rabbits, divided into three groups, were treated for 30 days with the following combinations of drugs: bimatoprost 0.03% + timolol 0.5%, travoprost 0.004% + timolol 0.5% and latanoprost 0.005 + timolol 0.5%. The right eyes served as controls and received no medication. At the end of the experiment, after enucleation, the conjunctivas were assessed through histomorphometry (number of inflammatory and goblet cells, epithelial thickness) and immunohistochemistry (anti-actin antibody to assess the degree of fibrosis). RESULTS: Histomorphometrically, there was infiltration of inflammatory cells in all the treated eyes. An increased number of goblet cells was observed with the use of all fixed combinations of prostaglandin analogues associated with timolol maleate in comparison with the control group. The combination travoprost + timolol resulted in more intense fibrosis. The effect of bimatoprost + timolol caused an intermediate reaction pattern among the other drugs, fostering higher numbers of goblet cells in the conjunctival epithelium, more than the other fixed combinations in this study. There was a difference in the comparison of goblet cells of eyes treated with bimatoprost + timolol (16.11 ± 2.42) and of those treated with latanoprost + timolol (13.18 ± 1.60) (P = 0.016). CONCLUSION: It was found that all fixed combinations of prostaglandins analogues + timolol induce a reaction in the conjunctiva, increasing the inflammatory infiltrate.